Lake George [videorecording (DVD)] - Whigham, Shea, 1969-; Coon, Carrie, 1981-; Casella, Max (Magnolia Home Entertainment, 2025)
Two misfit oddballs embark on a road trip, strike a dubious deal too enticing to refuse, and find redemption amid shady circumstances.